Використання дедуктивних та індуктивних логічних умовиводів у системах штучного інтелекту - Мащенко, А. Р. (ХНУРЕ, 2023)
Nowadays the artificial intelligence systems tend to expand. Inferences play an important role in process of implementing the artificial intelligence systems, such as expert systems. Inferences are basement for creating systems of logical rules, which are based on the processing of raw data and knowledge to obtain conclusions. This work considers the integration of deductive and inductive reasoning with particular suite of rules in artificial intelligence, which allows to ensure the efficiency and accuracy of decision-making.